2017
DOI: 10.3390/nu9080825
|View full text |Cite
|
Sign up to set email alerts
|

The Linoleic Acid: Dihomo-γ-Linolenic Acid Ratio (LA:DGLA)—An Emerging Biomarker of Zn Status

Abstract: Zinc (Zn) deficiency is a common aliment predicted to affect 17% of the world’s population. Zinc is a vital micronutrient used for over 300 enzymatic reactions and multiple biochemical and structural processes in the body. Although whole blood, plasma, and urine zinc decrease in severe zinc deficiency, accurate assessment of zinc status, especially in mild to moderate deficiency, is difficult as studies with these biomarkers are often contradictory and inconsistent. Hence, as suggested by the World Health Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 67 publications
4
39
1
2
Order By: Relevance
“…Furthermore, Zn modifies cyclooxy-genase activity and it acts as a co-enzyme for ∆6 desaturase [31][32][33]39]. The link between the ∆6 desaturase and Zn has been studied both in animals and humans [32,34,35,39]. The LA:DGLA ratio has been proposed as a potentially new biomarker of Zn status as it has been demonstrated that the ratio changes in accordance to dietary Zn manipulations [32,33,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Zn modifies cyclooxy-genase activity and it acts as a co-enzyme for ∆6 desaturase [31][32][33]39]. The link between the ∆6 desaturase and Zn has been studied both in animals and humans [32,34,35,39]. The LA:DGLA ratio has been proposed as a potentially new biomarker of Zn status as it has been demonstrated that the ratio changes in accordance to dietary Zn manipulations [32,33,39].…”
Section: Discussionmentioning
confidence: 99%
“…Trace elements have a role in FA metabolism. Zn is a cofactor for desaturases and elongases in endogenous FA synthesis [30][31][32][33][34][35], so the alterations in plasma levels of Zn possibly influence the activities of these enzymes and consequently the regulation of FA metabolism. Serum concentrations of Zn and Fe correlated with serum PUFA concentrations and activities of certain desaturases [36][37][38].…”
mentioning
confidence: 99%
“…3C). As the LA:DGLA is a sensitive novel biomarker for evaluating Zn status 74 , these results suggest that longer-term (6 months) exposure to 'Biofortified' diet may demonstrate clearer improvements to Zn status and is warranted. Zinc deficiency in chickens is known to negatively alter the gut microbiome, and improved microbial composition in 'Biofortified' chickens may be an additional symptom of improved Zn status 75 .…”
Section: Discussionmentioning
confidence: 88%
“…C18:0 iso may be a microbial product of a branched chain amino acid and a branched short chain fatty acid [35]. C20:3n-6 (dihomo-gammalinolenic acid, DGLA) can be made from LA by the host [36] and is a precursor of the antiinflammatory and anti-proliferative prostaglandin PGE 1 [37][38][39]. Therefore, microbial modulation of DGLA may represent a mechanism by which the microbiome impacts inflammatory conditions and cancer development.…”
Section: Discussionmentioning
confidence: 99%